Pendidikan multikultural-religius untuk mewujudkan karakter peserta didik yang humanis-religius (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2012)
The term of multicultural education, religious education contains of two concepts combined, i.e between multicultural education and religious education. Multicultural education as the basis of education values cultural diversity. Whereas, the religious education is as a basis of education on religious values to produce religious men. The combination of these two concepts of education aims to make an educational system that integrates from both of them, or reduce the advantages, especially to produce religious humanist students in a good character. Istilah pendidikan multikultural-religius mengandung dua konsep pendidikan yang dipadukan, yaitu antara pendidikan multikultural dan pendidikan agama. Pendidikan multikultural sebagai basis pendidikan yang menghargai kemajemukan budaya sedangkan pendidikan agama sebagai basis pendidikan yang bersumberkan pada nilai-nilai keagamaan untuk melahirkan manusia-manusia religius. Perpaduan dua konsep pendidikan ini bertujuan untuk dapat membangun sistem pendidikan yang dapat mengintegrasikan dari keduanya atau mengurangi kelemahannya,khususnya untuk mewujudkan karakter peserta didik yang humanis dan religius.